Mechanisms of natural killer cell cytotoxicity - Watzl, Carsten (Henry Stewart Talks, 2023)
Natural killer (NK) cells can kill infected or transformed cells, Cytotoxic activity and target cell adhesion, Integrin mediation, Immunological synapse formation, Cell apoptosis via lytic granule exocytosis, NK cell expression of FasL or TRAIL, Death receptor-mediated apoptosis, Single force cell spectroscopy, Granzyme B, Caspase 8